Experimental and numerical evaluation of temperature variation by frictional heating at the interface between snow and ski - Okajima, J.; Okabe, T.; Miyamoto, N.; Morimoto, T.; Tsunoda, K.; Hatakeyama, N. (Journal of Biomechanical Science and Engineering, 2020)
To evaluate the frictional heating effect during ski gliding by temperature measurement, a temperature measurement system was developed and evaluated numerically and experimentally. The portable temperature measurement system with high temperature resolution and accuracy consisted of thermistors and a portable logger with a 24-bit A-D convertor. The thermistors were inserted in a hole in the ski board with thermal conductive adhesive. By using numerical simulation, the difference between the interface temperature and the averaged temperature in the sensing region was evaluated. The temperature difference was proportional to the value of frictional heat generation, and the maximum difference in the experimental range in this study was 0.17 K. To test the developed system, a gliding experiment was conducted at Shinjo Cryospheric Environment Laboratory. Three thermistors were installed in the ski board, and a moving object was constructed on the ski. By pulling the moving object with a guide wire, the moving object was glided, and the interfacial temperature was recorded. In the case of a total weight of 54 kg, which was near the optimal weight, the thermistor installed near the heel position had a large increment of temperature. In addition, similar temperature increments were observed during the acceleration phase of the moving object. After the acceleration phase, the gradient of the temperature increment changed. It was inferred that the variation of gradient was affected by the variation of the force balance on the moving object. This suggests that the local contact condition and friction might be estimated through temperature measurement.